On fluxed instantons and moduli stabilisation in IIB orientifolds and F-theory - Grimm, Thomas W.; Kerstan, Max; Palti, Eran; Weigand, Timo (Arxiv, 2011)
We study the superpotential induced by Euclidean D3-brane instantons carrying instanton flux, with special emphasis on its significance for the stabilisation of Kahler moduli and Neveu-Schwarz axions in Type IIB orientifolds. Quite generally, once a chiral observable sector is included in the compactification, arising on intersecting D7-branes with world-volume flux, resulting charged instanton zero modes prevent a class of instantons from participating in moduli stabilisation. We show that instanton flux on Euclidean D3-branes can remove these extra zero modes and helps in reinstating full moduli stabilisation within a geometric regime. We comment also on the F-theoretic description of this effect of alleviating the general tension between moduli stabilisation and chirality. In addition we propose an alternative solution to this problem based on dressing the instantons with charged matter fields which is unique to F-theory and cannot be realised in the weak coupling limit.
Gesehen am 19.12.2017